Содержание интерлейкинов сыворотки крови у детей, больных хроническим пиелонефритом: связь с длительностью заболевания, частотой и активностью обострений - Слободян, Е.И. (Таврический медико-биологический вестник, 2013)
Нами обстежено 60 дітей у віці від 6 до 16 років, хворих на хронічний пієлонефрит. Визначали
вміст інтерлейкінів сироватки крові в залежності від різних характеристик перебігу захворювання. Виявлено
залежність значень IL10 і IL17 від тривалості захворювання, частоти його загострень і їх активності, IL12
від частоти загострень та активності, а IL4 тільки від частоти загострень, що вказує на дисфункцію Th1,
Th2 і Th17-субпопуляцій Т-хелперів і свідчить про глибокі порушення в системі клітинного та гуморального
імунітету. We have examined 60 children aged 6 to 16 years with chronic pyelonephritis and established the content
of interleukins in the blood serum as function of different characteristics of the disease. We have revealed that
the IL10 and IL17 values depend on the duration of the disease, frequency of exacerbations and their activity,
the of IL12 values depend on the frequency of exacerbations and their activity, and the IL4 values only
depend on the frequency of exacerbations, which indicates dysfunction of Th1, Th2 and Th17 subpopulations
of T-helper cells and shows deep violation of the cellular and humoral immunity.